Identifikasi Frekuensi dan Intensitas Bunyi Alat Musik Kendang Kempul Banyuwangi sebagai Rancangan Bahan Ajar Fisika - Erika Yolanda Friselya (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Kendang Kempul music is an original Banyuwangi art that is spread across Banyuwangi Regency, which until now is played with several modern and traditional musical instruments such as kendang and kempul. Kendang and kempul are related to the amount of sound waves, namely frequency and sound intensity. The purpose of this research is to identify the frequency and intensity of sound on the Kendang Kempul Banyuwangi musical instrument and its existence, as well as to design teaching materials on the concept of frequency and intensity of sound on the Kendang Kempul Banyuwangi musical instrument. Data collection was done by interview, observation, and documentation. Data were analyzed through four stages, namely data collection, data reduction, data display, and conclusion drawing/verification. Frequency values and sound intensity levels were obtained from WavePad Sound Editor software, then average analysis was conducted. Furthermore, the intensity level value was converted into sound intensity. This study found that the sound of the drum depends on the size, hitting point and tightness of the rope, while the sound of the kempul depends on the type of kempul and the hitting point. This can be seen from the difference in measured sound frequencies. The intensity of the drum and kempul sound is inversely proportional to the distance of the listener from the sound source. The farther the distance, the weaker the sound. The results of this study can be integrated in the design of physics teaching materials.
Finalisasi_Maya_9 Juni 2026
Keywords: Frequency; Intensity; Kendang Kempul; Sound